Effects of probiotic supplementation on the growth performance of Thai silver barb (Barbonymus gonionotus) (Bleeker, 1850) fry - Mondal, Debashis Kumar; Rahman, Tanvir; Paul, Sagar; Islam, Md Jakiul; Miah, Idris (Fundamental and Applied Agriculture, 2019)
A six-week long feeding trial was performed with fifteen rectangular glass aquaria (35 L capacity) containing 180 fish (average weight 1.02±0.3 g) to evaluate the effects of probiotic supplementation on the growth performance of Thai silver barb, Barbonymus gonionotus fry. The fry were fed twice-a-day at 8-10% of their body weight. Three available commercial probiotics were added with commercial crumbled feed in three forms; (i) feed + 3% ‘Biofav aqua’ (T1), (ii) feed + 3% ‘NavioPlus’ (T2), (iii) feed + 3% ‘Eskalina’ (T3), whereas, water additive probiotic ‘ARIAKE3’ (T4) was added directly to water and feed without probiotics was control (T5). Results revealed that water quality parameters were best in T4 compared to others. Net weight gain (3.46 g), percent weight gain (361.67%), (SGR) (3.63%) and survival (100%) were significantly higher (p<0.01) in T4. FCR (2.06) (p<0.05) and PER (1.34) (p<0.01) were significantly lowest but FCE (0.48) was significantly (p<0.05) highest in T2 compared to others. Control showed lower growth and feed utilization efficiency compared to probiotics supplemented treatments. Whole body protein, lipid and carbohydrate content were also found highest in T4. In the present study, the addition of probiotics in the regular diets significantly increased the growth and survivability of this commercially important fish. However, considering the growth, food efficiency and the water quality index, the water additive probiotic showed more beneficial effects for the monoculture of the selected fish which may be used in commercial farming for better growth performance of B. gonionotus.